Pharmacological Treatment in the Management of Chronic Subdural Hematoma - Wang, Xing; Song, Jinlei; He, Qiang; You, Chao (Frontiers in Aging Neuroscience, 2021)
Background: Several pharmacological treatments have been used to treat patients with chronic subdural hematoma (CSDH), although little is known about the comparative effectiveness of different classes of medication. We performed a Bayesian network meta-analysis to compare and rank the efficacy and safety of five drug regimens to determine the best treatment for this group of patients. Methods: We systematically searched PubMed, Medline, clinicaltrials.gov, the Cochrane database, and Embase to identify relevant randomized clinical trials (RCTs) comparing drug treatments in adult patients with CSDH. A network meta-analysis was conducted using a Bayesian framework. Random- and fixed-effects models were used to pool the network results, and the preferred model was selected by comparing the deviance information criteria (DIC). Efficacy outcomes included recurrence requiring surgery, changes in hematoma volume, and a good recovery. The safety outcomes were treatment-related adverse events and all-cause mortality. Results: In this Bayesian network meta-analysis, available data were obtained from 12 eligible trials, including 2,098 patients and 5 techniques. Compared to placebo, atorvastatin (RR: 0.45, 95% CrI: 0.24–0.81) and dexamethasone (RR: 0.38, 95% CrI: 0.22–0.63) were similarly effective in reducing recurrence requiring surgery by 55% and 62%, respectively. Dexamethasone (RR: 0.46, 95% CrI: 0.23–0.91) was more effective in reducing recurrence requiring surgery than goreisan. Additionally, atorvastatin reduced the hematoma volume to a greater extent than placebo (MD: −7.44, 95% CrI: −9.49 to −5.43) or goreisan (MD: −14.09, 95% CrI: −23.35 to −4.82). Moreover, tranexamic acid (MD: −12.07, 95% CrI: −21.68 to −2.29) reduced the hematoma volume to a greater extent than goreisan. No significant differences were detected between drugs and placebo with regard to a good recovery. In terms of safety, dexamethasone (RR: 1.96, 95% CrI: 1.20–3.28) increased the risk of mortality compared to placebo. Conclusion: These findings suggest that dexamethasone is the best treatment to reduce recurrence and atorvastatin is the best treatment to reduce hematoma volume in patients with CSDH. However, clinicians should pay close attention to the elevated risk of all-cause mortality and potential adverse events caused by dexamethasone. Future well-designed RCTs with more participants are needed to verify these findings. Clinical Trial Registration:http://osf.io/u9hqp.